Common Factors Responsible for Uncontrolled Epilepsy Patients attended at a Tertiary Care Hospital in Bangladesh - Mian, Md Ferdous; Hussain, Mohammad Enayet; Islam, Md Nahidul; Khan, AFM Al Masum; Chowdhury, Rajib Nayan; Habib, Mansur; Mohammad, Quazi Deen (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Epilepsy is a common neurological disorder. It is estimated that there are at least 1.5 to 2 million epilepsy patients in Bangladesh3. Many of these patients are suffering from uncontrolled epilepsy which leads to cognitive deterioration, psychosocial dysfunction and increased morbidity and mortality. The causes behind uncontrolled epilepsy are multifactorial. Some are patient-related, some physician-related and some are medication-related. Objective: The purpose of the present study was to identify the factors responsible for uncontrolled epilepsy. Methodology: This case-control study was carried out in the epilepsy clinic of the Dhaka Medical College Hospital, Dhaka, Bangladesh from July 2010 to June 2012 (2 years). A total of 100 patients of which 50 consecutive patients of uncontrolled epilepsy (cases) and 50 age-matched controls with well controlled epilepsy (control) were recruited. Patients were interviewed according to a preformed questionnaire. Results: The mean ages of case and control groups were 21.84 ± 8.70 and 23.94 ± 10.28 years (p=0.273). The male female ratio was almost equal in both groups. The factors which turned out significant (p value <0.05) for uncontrolled epilepsy were lack of support from the family (p=0.032), lack of motivation about the disease (p=0.001), unavailability of drugs (p=0.001), irregular intake of anti-epileptic drugs (p=0.001), stopping AEDs willingly after transient control of seizures (p=0.001), lack of knowledge about the disease (p=0.003), treatment duration (p=0.005) & prognosis of the disease (p=0.026). Other factors were low annual income of the family (p=0.001), occupation (p=0.040), lower educational status (p=0.027) and residence in rural area (p=0.016). Important patient related factors were earlier age of onset of seizure (p=0.027), higher initial seizure frequency (p=0.012), associated clinical features (neurological deficits, mental retardation, behavioral abnormality) (p=0.030), abnormal brain imaging findings (p=0.013) and non response to first anti epileptic drug (p=0.005). Conclusion: Many of the factors behind uncontrolled epilepsy can be minimized by proper counseling of the patient at the start of treatment and regular follow up. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 42-47